2004
DOI: 10.1159/000077680
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Serum p53 Antibodies during Follow-Up after Treatment of Invasive Bladder Tumors

Abstract: Introduction: To investigate the prognostic importance of the changes in serum p53 antibody titrations during follow-up of patients who had anti-p53 antibody-positive invasive bladder tumors with transitional epithelial cells. Materials and Methods: The study group consisted of 23 clinically T3≤, N0, M0 patients with positive serum anti-p53 antibodies before treatment. 23 cases with negative serum anti-p53 antibodies who were comparable in age, comorbidity and stage with the study group were selected as a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Several studies have reported that patients negative for p53 Abs at the time of diagnosis did not become positive during follow-up. 25,26 Gumus et al 27 recently found no change in serum p53 Abs during the follow-up of 23 patients with invasive bladder tumors who were negative for p53 Abs before treatment, regardless of outcome, and they suggested that it was suffi cient to monitor the status of serum p53 Abs only in patients positive for serum p53 Abs at the time of diagnosis. We agree with this conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that patients negative for p53 Abs at the time of diagnosis did not become positive during follow-up. 25,26 Gumus et al 27 recently found no change in serum p53 Abs during the follow-up of 23 patients with invasive bladder tumors who were negative for p53 Abs before treatment, regardless of outcome, and they suggested that it was suffi cient to monitor the status of serum p53 Abs only in patients positive for serum p53 Abs at the time of diagnosis. We agree with this conclusion.…”
Section: Discussionmentioning
confidence: 99%